The polifarmacy and quality of life in health (SF-36) of the staff in removal situation of the military health center. - Quispe Valdez, Maycol Janns (2020)
Polypharmacy and Health Quality of Life (SF-36) of retired personnel of the Tacna Military Health Center, 2018. The members of the sample were 150 participants, between Officers and Sub Officers with chronic diseases. A data collection sheet and the content analysis technique were used for the independent variable "Polypharmacy" and for the dependent variable "Quality of Life in Health" the SF-36 Health questionnaire was used, consisting of 36 scale questions Likert and dichotomous type, and the personal interview technique. Research of observational, prospective, relational level. Of the 150 respondents, 22% are in the category of "Without Polypharmacy" and 78% in the category "With Polypharmacy"; For the contrast of the hypotheses, the non-parametric statistical test of punctual biserial correlation was used, obtaining the following results: the dimensions of the quality of life of the staff in a situation of retirement worse valued in the population were physical role (mean 12.8); that polypharmacy is associated with the quality of life in terms of the Physical Health Summary Component. Polypharmacy is not associated with the Summary Mental Health Component. Finally, it is concluded that the Polypharmacy and Quality of Life in Health of retired personnel of the Tacna Military Health Center, 2018, demonstrates the existence of a direct association (p: 0.014).